Mediation Effect of Work Stress on the Relationship between Role Conflict, Role Ambiguity, and Employees Performance - Tri Wahjoedi (LPPM Universitas Terbuka, 2023)
Purpose – The aim of this study was to examine how role conflict and role ambiguity, mediated by work stress, influenced employees performance. Methodology – A quantitative analysis was performed by using the Slovin formula for a total sample of 114 employees from PT MSP, a prominent household appliances company in East Java, Indonesia. The collected data were analyzed using SEM SmartPls-3. Results – The results showed that both role conflict and role ambiguity exerted a significant negative impact on employees performance, and also contributed to increased work stress. Moreover, work stress showed a significant negative impact on employees performance. The inclusion of work stress as an intermediary highlighted its role in mediating the negative relationship between role conflict, role ambiguity, and employees performance. Originality – Incorporating work stress as a mediator in the connection between these variables enriched the exploration of the interrelation. This intricate relationship required a deeper understanding for the optimization of employees performance.